CONSTITUTION - THE BASIC LAW GUARANTEEING THE RIGHTS OF ENTREPRENEURIAL FARMERS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article examines the role, content and essence of the Constitution of the Republic of Uzbekistan, the Law "On Farming" in improving the activities of farms in Uzbekistan. The adoption of laws regulating the agricultural sector in our Republic from the first days of independence and their significant aspects are analyzed.